Novel Process Methods for the Whole Cottonseed: Effect on the Digestibility, Productivity, Fat Profile, and Milk Gossypol Levels in Lactating Dairy Cows - Sun, Xiaoge; Su, Yitong; Hao, Yangyi; Zhang, Jun; Yue, Xiaomei; Wang, Wei; Ma, Zhu; Chu, Kangkang; Wang, Shuang; Wang, Yajing; Li, Shengli (Frontiers in Nutrition, 2022)
In this study, we aimed to determine the effect of mixed-process methods on the ruminal degradability of whole cottonseed (WCS) both in situ and in vitro, and the effect on the production performance of dairy cows. Eight WCS process methods were tested on the ruminal digestibility, including crush-alkali 1 (CA1), crush-alkali 2 (CA2), crush-alkali 3 (CA3), alkali 1-crush (A1C), alkali 2-crush (A2C), alkali 3-crush (A3C), crush-only (CO), and non-processed. Alkali 1, 2, and 3 indicate the supplementation of alkali to WCS at the dose of 4% on dry matter (DM) base as followed: 4% NaOH, 2% NaOH + 2% CaO, and 2% NaOH + 2% CaCl2 alkaline, respectively. Among all treatments, CA2 showed the highest WCS ruminal degradation in situ and the highest intestinal digestibility of WCS in vitro. Furthermore, an animal experiment was conducted for 60 days on 30 Holstein dairy cows, using a diet without WCS (CON group), a diet containing 8% non-processed WCS (NP group), and a diet containing 8% CA2-treated WCS (CA2 group). The results indicated that the dry matter intake, 4% fat-corrected milk production, milk protein, milk fat, and content of short-chain saturated fatty acid of milk in the CA2 group were significantly higher (P < 0.05) than CON group. Furthermore, DMI, the CLA was significantly greater (P < 0.05) in the CA2 group than the other groups. Additionally, the free gossypol concentration in serum or milk was under safety level in the three groups. Overall, crush and alkalization (NaOH: CaO = 1:1) treatment could improve the utilization of WCS in dairy farms.